65 FATTY ACIDS ACTIVATE NUCLEAR FACTOR κB AND INDUCE INTERLEUKIN-6 PRODUCTION FROM MOUSE 3T3-L1 PREADIPOCYTES AND ISOLATED HUMAN SUBCUTANEOUS STROMAL-VASCULAR CELLS. (1st March 2007) - Tu, P.; Wong, S.; Bigornia, S.; Corkey, B.; Apovian, C.; Guo, W.
Abstract : Obesity markedly elevates circulating proinflammatory cytokines, which are found to be associated with multiple chronic diseases, such as cardiovascular diseases and type 2 diabetes mellitus. However, the underlying mechanisms for systemic inflammation in obese individuals are poorly understood. One unambiguous physiologic change from lean to obese individuals is a chronic elevation of circulating free fatty acids (FFAs), imparted owing to enlarged fat cell size and population as well as impaired antilipolytic actions of insulin. FFA has been shown to induce cytokine production in several cell types, including macrophages. Obesity is found to be associated with increased macrophage infiltration in adipose tissue, but the cause of such is still not conclusive. On the other hand, adipose tissue is naturally enriched with preadipoctyes. Striking similarity has been documented between preadipocytes and macrophage with even conversion between the two cell types under adequate conditions. Paradoxically, little is known about how FFA affects the function of preadipocytes, the cell type that is closely associated with adipocyte-derived FFA. In this study, we showed that FFA directly activates NF-κB, the master proinflammatory transcription factor and its downstream products IL-6 and TNF-α in clonal preadipocytes (3T3-L1) and in isolated human adipose stromal-vascular cells (SVCs). Inhibition of NF-κB using NF-κB-specific inhibitor (TLCK), proteasome inhibitor (MG132), and siRNA-mediated inhibition of NF-κB-p105 significantly attenuated FFA-stimulated IL-6 production in both 3T3-L1 and human SVAs ( p < .05 for all). Taken together, our findings suggest that FFA may play an active role in adipose inflammation in obese individuals via regulation of function of preadipoctyes.